Personalized drug therapy in psychiatry: Maybe a little old or a little new, but the treatment of future - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2010)
Most of current drugs are developed and approved on the basis of their safety and effectiveness in large group of people and they can be prescribed to any patient based on the diagnosis. Despite increased number of available psychotropic drugs today, these drugs are still not enough to treat the whole spectrum and severity of psychiatric disorders. Besides, they show significant individual variations among patients. Because of that the concept of 'personalized therapy' has been developed in recent years. Among many factors that have contributed to the development of personalized drug therapy, it is thought that advances in the molecular biology have played the most significant role so far. The concept of personalized drug therapy, which relies on genetic and molecular biology research, has become the most important issue in psychopharmacology. Although single nucleotide polymorphisms are known to cause variations in drug responsiveness among individuals, most psychiatric disorders, including schizophrenia, major depression, and bipolar disorder, are considered polygenic in etiology. Retrospective evaluation of the data up to date provides further support for personalized drug therapy in psychiatry in adjusting therapeutic doses, predicting responses reducing adverse drug reactions, making early diagnoses, and developing personal health plans. In summary, personalized drug therapy, which can also be expressed as treat the patient, not the disease is not an easy task in the era of guidelines, protocols, and treatment algorithms.
Keywords: Pharmacogenetics; drug response; biomarkers; adverse drug reactions; personalized drug therapy; psychiatry; PHARMACOGENETICS; ANTIPSYCHOTICS; PHENOTYPE